Gender as a Political Resource in Social Citizenship (The Role of Women in the Indonesian Parliament) - Mariana; Ahmad Rifai (Zona Law And Public Administration Indonesia, 2023)
Women's political presence in the public sphere, including their political participation and representation, is an important, though not equal element for Indonesian citizens in their capacity as participatory and sufficient in multiple strategies to create gender equality. This paper aims to find out about gender as a political source in social citizenship, especially the role of women in the Indonesian parliament. The legal materials used in this study include primary, secondary, and tertiary legal materials. The collection of secondary legal materials is carried out by literature studies. The existence of women in parliament gives a new spirit in the gender equality order as policy makers on governance issues. In its existence, affirmative action is still a problem for women in improving the quality of their representation in parliament.